Assessment of Public Hospital Governance in Romania: Lessons From 10 Case Studies - Antonio Duran; Tata Chanturidze; Adrian Gheorghe; Antonio Moreno (Kerman University of Medical Sciences, 2019)
Background The Government of Romania commissioned international technical assistance to help unpacking the causes of arrears in selected public hospitals. Emphases were placed on the governance-related determinants of the hospital performance in the context of the Romanian health system.   Methods The assessment was structured around a public hospital governance framework examining 4 dimensions: institutional arrangements, financing arrangements, accountability arrangements and correspondence between responsibility and decision-making capacity. The framework was operationalized using a 2-pronged approach: (i) a policy review of broader health system governance arrangements influencing hospital performance; and (ii) a series of 10 case-studies of public hospitals experiencing financial hardship. Data were collected during 2016-2017 through key informant interviews with central authorities and hospital management teams, exhaustive semi-structured questionnaires filled in by hospitals, as well as the review of documentary sources where feasible.   Results Overall, the governance landscape of Romanian public hospitals includes a large number of seemingly modern legislative provisions and management instruments. Over the past 30 years substantial efforts have been made to put in place standardised hospital classification, hospital governance structures, management and service purchasing contracts with key performance indicators, modern reimbursement mechanisms based on diagnosis-related groups (DRGs), and regulatory requirements for accountability, including internal and external audit. Nevertheless, their application appears to have been challenging for a range of reasons, pointing to the misalignment between the responsibility and decision-making capacity given to hospitals in a questionably conducive context. Incoherent policy design, outdated and often disjointed regulatory frameworks, and cumbersome administrative procedures limit managerial autonomy and obstruct efficiency gains. In a context of chronic insufficient funding, misaligned incentives, and overly rigid service procurement processes, hospitals seem to struggle to adjust service baskets to the population's health needs or to overcoming financial hardship. External challenges, combined with the limited strategic, operational, and financial management capacity within hospitals, make it difficult to exhibit good financial and general performance.   Conclusion Existing governance arrangements for Romanian public hospitals appear conducive to poor financial performance. The suggested framework for hospital governance assessment has proved a powerful tool for identifying system and hospital-specific challenges contributing to sub-optimal hospital performance.